Seroprevalance of Babesia ovis in sheep in Malatya - Aktas, M; Düzgün, A; Babür, C (Scientific Technical Research Council Turkey, 2001)
This study was carried out in Malatya and vicinity to determine the seroprevalance of Babesia ovis in sheep. A total of 220 sheep sera were tested against B, ovis using the Enzyme-Linked Immunosorbent Assay (ELISA). in addition, peripheral blood smears from these sheep were prepared and examined for B. ovis. The ELISA test showed that 55.9% of sheep were seropositive for B. ovis infection. The infection rate was 49.2% in sheep which were 1-12 months old and 59% in sheep which were older than one year. In the microscopic examination of blood smears, four out of 220 sheep were found to be infected with Babesia ovis.
Malatya Yöresinde Koyunlarda Babesia ovis'in Seroprevalansi
Keywords: Babesia ovis; ELISA; sheep